Management of Multisystem Inflammatory Syndrome in Children (MIS-C) in resource limited settings: The Kenyan Experience - Angela Migowa; Pauline Samia; Sean del Rossi; Oliver Ombeva Malande; Jasmit Shah; Chemutai Kenei; Joy Ayaya; Daisy Jeruto; Laura Oyiengo; Laura Lewandowski (Pediatric Rheumatology Online Journal, 2022)
Abstract Background Since the onset of the recent COVID-19 pandemic, there have been growing concerns regarding multisystem inflammatory syndrome in children (MIS-C). This study aims to describe the clinico-epidemiological profile and challenges in management of MIS-C in low-middle income countries by highlighting the Kenyan experience. Methods A retrospective study at the Aga Khan University Hospital Nairobi, Avenue Hospital Kisumu and Kapsabet County Referral Hospital was undertaken to identify cases of MIS-C. A detailed chart review using the World Health Organization (WHO) data collection tool was adapted to incorporate information on socio-demographic details and treatment regimens. Findings Twenty children with MIS-C were identified across the three facilities between August 1st 2020 and August 31st 2021. Seventy percent of the children were male (14 of 20). COVID-19 PCR testing was done for five children and only one was positive. The commonest clinical symptoms were fever (90%), tachycardia (80%), prolonged capillary refill (80%), oral mucosal changes (65%) and peripheral cutaneous inflammation (50%). Four children required admission into the critical care unit for ventilation support and inotropic support. Cardiac evaluation was available for six patients four of whom had myocardial dysfunction, three had valvulitis and one had pericarditis. Immunoglobulin therapy was availed to two children and systemic steroids provided for three children. There were no documented mortalities. Interpretation We describe the first case series of MIS-C in East and Central Africa. Majority of suspected cases of MIS-C did not have access to timely COVID-19 testing and other appropriate evaluations which highlights the iniquity in access to diagnostics and treatment.